2016
DOI: 10.1177/0886260516635322
|View full text |Cite
|
Sign up to set email alerts
|

Raising a Red Flag on Dating Violence: Evaluation of a Low-Resource, College-Based Bystander Behavior Intervention Program

Abstract: Encouraging bystanders to intervene safely and effectively in situations that could escalate to violence-known as bystander behavior programs-is a growing yet largely untested strategy to prevent dating violence. Using a quasi-experimental design, we evaluate a low-resource, low-intensity intervention aimed at preventing dating violence among college students. The integrated behavioral model (IBM) was used to guide the evaluation. We also assess which IBM variables were most strongly associated with bystander … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
(46 reference statements)
3
25
0
Order By: Relevance
“…Nevertheless, such positive evidence contrasts with the findings of other studies which have shown a lack of efficacy regarding the intent to help, self-efficacy, social norms, attitudes related to dating violence (Borsky et al, 2018), rape myth acceptance, and utilization of bystander behaviors (Moynihan et al, 2011). Furthermore, mixed results on utilization of bystander behaviors (Katz, Heisterkamp, & Fleming, 2011;Miller et al, 2012) and willingness to intervene (Miller et al, 2012) have been found.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Nevertheless, such positive evidence contrasts with the findings of other studies which have shown a lack of efficacy regarding the intent to help, self-efficacy, social norms, attitudes related to dating violence (Borsky et al, 2018), rape myth acceptance, and utilization of bystander behaviors (Moynihan et al, 2011). Furthermore, mixed results on utilization of bystander behaviors (Katz, Heisterkamp, & Fleming, 2011;Miller et al, 2012) and willingness to intervene (Miller et al, 2012) have been found.…”
Section: Introductionmentioning
confidence: 59%
“…The current study extends prior research by examining the short-term effects of a peer-and bystander approach-based intervention to improve the intent to offer help, empathy, and bystander attitude outcomes at the level of the individual in response to dating violence in a Brazilian sample of adolescents. While the intention to help (Amar et al, 2015;Borsky et al, 2018;Miller et al, 2012;Peterson et al, 2018) and bystander attitudes (Amar et al, 2015) have been investigated in previous studies, empathy has been poorly explored in studies evaluating bystander interventions for preventing dating violence, though there is evidence for it as one of the protection factors for dating violence (McCloskey & Lichter, 2003) and it is considered an outcome of interest in bystander interventions in other types of violence (Jenkins & Nickerson, 2017). These short-term outcomes were considered precursors of medium-term (helpseeking and help-offering between friends in dating violence situation and friendship quality) and longterm (number of friends who are perpetrators and victims of dating violence and victimization and perpetration of dating violence) outcomes ( Fig.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Baxter and Montgomery (1996), when individuals decide whether to disclose information four risks are present: rejection, reduction of personal autonomy and integrity, loss of control or self-efficacy and hurting or embarrassing the listener. With these risks in mind, Shirley, Powers and Sawyer (2007) found that when individuals believe they are being psychologically abused they disclose less often, and when they do disclose they tend to be dishonest about the realities of their situation.…”
Section: Domestic Violence and Problems Of Disclosurementioning
confidence: 99%
“…In order to address these problems, it is essential for institutions of higher education to take necessary steps and address these problems. One strategy to prevent dating violence (and IPV) on college campuses is to focus on intervention efforts targeting the bystanders (Borsky, McDonnell, Turner, & Rimal, 2016). This can be accomplished by implementing prevention programs that train students from being potential bystanders to those who can step-in to help diffuse risky situations, identify and challenge perpetrators, and assist in support of victims (Moynihan, Banyard, Cares, Potter, Williams, & Stapleton, 2015).…”
Section: College and University Levelmentioning
confidence: 99%